Fluorescence characterization of the precuring of impregnated fluffed veneers and bonding strength of scrimber in relation to drying conditions. Issue 2 (11th January 2022) - Guan, Mingjie; Tang, Xinyuan; Du, Keke; Liu, Jinzhang; Li, Shuangchang
Abstract: To study the effect of the precuring rate of impregnated fluffed veneers (IFVs) on the bonding performance of scrimber, the precuring rate of IFVs following different drying conditions was characterized by fluorescence microscopy. The phenol formaldehyde (PF) solid content, drying temperature, and time were assessed using orthogonal tests. The moisture content, precuring rate of the dried IFVs, and bonding strength of the scrimber were evaluated. The results showed that the moisture content of the IFVs was mainly affected by the PF solid content, while the precuring rate of the impregnated IFVs was primarily impacted by the drying temperature. A solid PF content of 20% and optimum drying conditions of 60 °C and 1.5 h were associated with a precuring rate of 12.3% of the PF resin on the surface of the IFVs, obtaining scrimber with the best bonding performance of 2.95 MPa.